Micropropagation and callus induction of Lantana camara L. e A medicinal plant - Veraplakorn, Varaporn (Agriculture and Natural Resources, 2016)
Lantana camara L., a medicinal plant, exhibits antimicrobial, fungicidal, insecticidal and nematicidal properties. Effective in vitro micropropagation and callus induction aid plant material production for bioactive compound studies and plant resource conservation. Shoot multiplication, root induction and callus formation were investigated. The results indicated a high shoot multiplication rate on Murashige and Skoog (MS) medium supplemented with 16.0 µmol/L N6-benzyladenine (BA). Shoots showed good root regeneration with healthy plantlets on MS medium supplemented with 7.5 µmol/L indole-3-butyric acid. A large callus size occurred with roots at the basal end of shoots on the media added with 20.0 µmol/L or 40.0 µmol/L of 1-naphthalene acetic acid (NAA) combined with 40.0 µmol/L BA. Leaf explants were more suitable for callus induction. Media containing 0.0-40.0 µmol/L BA in combination with 20.0 µmol/L or 40.0 mmol/L NAA could efficiently induce callus formation with the same level of relative growth rate. These plants and callus will be suitable sources of plant material for further study in producing bioactive compounds.